A next generation emerging technologies roadmap for enabling collective computational intelligence in disaster management. (17th March 2011) - Bessis, Nik; Asimakopoulou, Eleana; Xhafa, Fatos
Much work is underway within the broad next generation emerging technologies community on issues associated with the development of services to foster synergies and collaboration via the integration of distributed and heterogeneous resources, systems and technologies. In previous works, we have discussed how these could help coin and prompt future direction of their fit-to-purpose use in various real-world scenarios including but not limited to disaster management, healthcare, vehicular networking and knowledge cities. In this exploratory paper, we brief and then build upon our previous works and specifically, we present a roadmap highlighting the possible use of next generation emerging technologies for enabling collective computational intelligence in managing disaster situations. A relevant scenario is used to illustrate the model architecture, as well as to detail the proposed roadmap.